Importance of the generic segment of thye plant protection products – the case of the Polish market - Stajszczak, Arkadiusz; Majewski, Edward (Applied Studies in Agribusiness and Commerce, 2017)
Authors present results of the analysis of developments in the plant protection products industry, with a focus on its generic part. Authors concentrate on long-term changes of prices, volumes and values of generic pesticides launched into the market. There were two strategic groups of producers identified: research and development (R&D) and generic. The analyses conducted prove that there is a relationship between the amount of generic products on the market and their prices. It is also clear that the number of competitors significantly influences the speed and range of price erosion. Used as examples generic plant protection products were placed on the market with an average price 15% lower comparing to branded pesticides. JEL code: M31